국제컨퍼런스 '행복한 삶 : 경제적 가치를 넘어' (헬레나 노르베리 호지,카르마 치팀,나오토 야마우치,고승희) - 헬레나 노르베리 호지, 카르마 치팀, 나오토 야마우치, 고승희 (충남발전연구원, 2012)
Nearly forty years ago, I watched as a culture that had been sealed off from the rest of the world was suddenly thrown open to economic development. Witnessing the impact of the modern world on an ancient culture gave me insights into how economic globalisation creates feelings of inadequacy and inferiority, particularly in the young, and how those psychological pressures are helping to spread the global consumer culture. Since that time I have been promoting the rebuilding of community and local economies as the foundation of an ‘Economics of Happiness’. - 이후 생략
Keywords: 국제컨퍼런스; 행복